Cyclic codes of length pn over (ℤp)m. (17th February 2021) - Mohammed, Mohanad Ali; Munshid, Ameer. J.; Alaeiyan, Mehdi
Abstract: The purpose of this paper is describing cyclic codes of length p n over (ℤ p ) m . We partition ideals of into two general forms and calculate the annihilator of these two forms. In this way, we can introduce an explanation of cyclic codes and the dual code of an arbitrary cyclic code of length p n over (ℤ p ) m .